'We need to know what's going on': Views of family members toward the sexual expression of people with dementia in residential aged care. (September 2014) - Bauer, Michael; Nay, Rhonda; Tarzia, Laura; Fetherstonhaugh, Deirdre; Wellman, David; Beattie, Elizabeth
This paper reports on a study which explored the views and attitudes of family members towards the sexual expression of residents with dementia in residential aged care facilities in two states in Australia. Recruitment was challenging and only seven family members agreed to an interview on this topic. Data were analysed using a constant comparative method. Family were generally supportive of residents' rights to sexual expression, but only some types of behaviours were approved of. There was an acknowledgement that responding to residents' sexuality was difficult for staff and many families believed that they should be kept informed of their relative's sexual behaviours and moreover be involved in decision making about it. Findings suggest the need for family education and a larger study to better understand the views and motivations of family carers and how these might impact on the sexual expression of the older person with dementia living in residential aged care.